2017
DOI: 10.1080/09593985.2017.1318423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fascia dry needling on non-specific thoracic pain – A proposed dry needling grading system

Abstract: This case report describes a 42-year-old female who presented with complaints of diffuse pain in her thoracic paraspinal region from T2 to T7. Physical examination revealed tenderness, increased turgor and restriction of her superficial fascia. A potential first time description of successful management utilizing fascia dry needling is described in this report with improvements noted in pain, range of motion, and functional activities. The patient was discharged from physiotherapy after four treatment sessions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This finding illustrates that, although the distribution of MNK therapy and acupuncture for treating AAS diverged from the theories of superficial fascia [ 55 , 56 ] and traditional Chinese medicine meridians [ 57 , 58 ], both demonstrated commendable therapeutic efficacy at the 1-month follow-up. This outcome could be attributed to both interventions’ ability to modulate neural reflex pathways, enhance local blood circulation, activate the immune system, and regulate the neuroendocrine system, thus manifesting clinical effectiveness [ 59 , 60 ]. As the present study found clinical efficacy differences, the conclusions drawn herein provide a reference for subsequent research.…”
Section: Discussionmentioning
confidence: 99%
“…This finding illustrates that, although the distribution of MNK therapy and acupuncture for treating AAS diverged from the theories of superficial fascia [ 55 , 56 ] and traditional Chinese medicine meridians [ 57 , 58 ], both demonstrated commendable therapeutic efficacy at the 1-month follow-up. This outcome could be attributed to both interventions’ ability to modulate neural reflex pathways, enhance local blood circulation, activate the immune system, and regulate the neuroendocrine system, thus manifesting clinical effectiveness [ 59 , 60 ]. As the present study found clinical efficacy differences, the conclusions drawn herein provide a reference for subsequent research.…”
Section: Discussionmentioning
confidence: 99%
“…While most commonly DN is directed at trigger points [2], its contemporary use also targets tendons [3,4], entheses [5], periosteum [6], scar tissue [7], and fascia [8] to reduce local and referred pain, lessen spasticity [9,10], eliminate neural entrapments [11], increase range of motion [12], or normalize muscle activation patterns [13]. DN is a safe anatomy-driven procedure [14], although there are inherent risks when safety precautions are not taken into account [15][16][17][18].…”
Section: Editorialmentioning
confidence: 99%
“…Worldwide, clinicians are using dry needling (DN) to reduce pain [1,2], increase range of motion and flexibility [3], enhance performance [4], reduce spasticity [5], or improve fascial and scar tissue mobility [6,7]. Dry needling is a safe and cost-effective treatment approach [8][9][10][11], but there is no literature informing clinicians whether DN can be applied safely in patients with altered coagulation.…”
Section: Introductionmentioning
confidence: 99%